The Mechanism of Developing a Sense of Belonging in Students Based on Integrative Approach - Arofatkhon, Ismailova; Korayev, S.B. (European Journal of Life Safety and Stability (2660-9630), 2023)
The purpose of the article is to demonstrate the effectiveness of project activities in the civil and patriotic education of future teachers. The study is based on an analysis of the implementation of projects of a pedagogical university that received grant support from various foundations. As a result, the article considers special abilities and skills as elements of project competence that are formed in the process of working on projects, as well as a positive trend in young people's attitude to the historical past of their native country, literature and culture of the state under the influence of participation in various university activities.